Transcendencja osoby w myśli filozoficznej kard. Karola Wojtyły = The transcendence of the human person in the philosophical thought of cardinal Karol Wojtyla - Sroczyński, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article the concept of the transcendence of the human person worked out by cardinal Karol Wojtyla is presented. The supremacy of human activity over activity of other beings is expressed in it. It manifests itself, according to Karol Wojtyla, in performing free, spirituals cognitive and appetitive acts. The description of transcendence accentuates the phenomenology of the human act as a cognitive and volitional act. The ultimate internal rationality of the person`s transcendence is, according to K. Wojtyla, her spirituality.
Keywords: Jan Paweł II, papież (1929-2005); transcendencja; filozofia człowieka; filozofia chrześcijańska